Organization of professional practices against intrafamily violence against children and adolescents in the institutional context - Gabriele Schek; Mara Regina Santos da Silva; Carl Lacharité; Maria Emília Nunes Bueno
ABSTRACT Objective: to analyze based on the practitioners' discourse, the way they organize their practices confronting situations of intra-family violence against children and adolescents. Method: qualitative research carried out with 15 professionals who work in social and health services located in the southernmost of Brazil. Data were collected through semi-structured interviews, performed at the participants' workplace. We used a theoretical matrix to analyze the data, based on Institutional Ethnography and the technique of discursive textual analysis. Results: the practitioners' practices developed in situations of intra-family violence against children and adolescents are organized on the basis of: power relations that take place in services that respond to violence situations; routines instituted to meet the demands of care in services; and the interplay between the conception of violence as a public health problem and the conception of violence as a social problem. Conclusion: the way these practices are organized is reflected in actions that are not protective against situations of intra-family violence against children and adolescents.